PENGARUH SENAM YOGA TERHADAP KREATIVITAS PADA DUA KELOMPOK MAHASISWA FAKULTAS PSIKOLOGI UNIVERSITAS PERSADA INDONESIA Y.A.I. - Agnes Irawati Kother (Universitas Bunda Mulia, 2011)
Creativity allows the emergence of new discoveries in science and technology. One effective way to increase creativity is a yoga exercise that will facilitate the function of the right hemisphere of the brain that is part of the brain that thinks creatively. Issues to be investigated in this study is: